A novel non-antimicrobial treatment of bacterial vaginosis: An open label two-private centre study. (January 2021) - Latham-Cork, Harriett C.; Walker, Kate F.; Thornton, Jim G.; Gunnarsson, Omar Sigurvin; Säfholm, Annette; Cardell, Monika; Strevens, Helena
Abstract: Background: Bacterial vaginosis (BV) is the most common cause of vaginal discharge. It is caused by an imbalance in the normal vaginal microbiota. Symptoms include an offensive odour. Standard oral or vaginal antimicrobial treatments have high immediate cure rates but almost as high recurrence rates. p Hyph, a vaginal pessary, contains glucono-delta-lactone (GDL) and sodium gluconate (NaG) which restore normal pH and disrupt the associated biofilm. Aim: To investigate the clinical performance of p Hyph, for both treatment and recurrence prevention. Design An open-label, single arm, multi-centre first in women study. Setting: Two private gynaecology clinics in Skåne County, Southern Sweden. Methods: Twenty four adult women with confirmed bacterial vaginosis received the investigational product for self-administration on days 0, 2, 4, and 6 and were assessed on day 7. Clinical cure was defined as absence of three of four Amsel's criteria ( p H excluded) on day 7. Safety and tolerability were also recorded. Those not cured by day 7 received a prolonged treatment protocol. Results There were three withdrawals, two before the day 7 assessment. 18/22 (82 %) were clinically cured at day 7. The pessary was well tolerated. Recurrence rates at 14 days in patients cured at day 7 after receiving standard study treatment (n = 18) were 1/18 (5.6 %) with no additional recurrences reported at 35 days. Three of four patients not cured at 7 days received continued treatment (day 7, 9, 11, and 13), but none were cured at 14 days. Conclusion: p Hyph has the potential for both high cure rates and a reduction in recurrence.